A Comprehensive Review of the Corrosion Behavior in Dissimilar aluminum alloys Welding of AA5xxx and AA6xxx - Setyawan, Hendra; Fahlovi, Oldy; Kurnia, Ganjar; Rasyda, Thriska Dewi Umi (International Journal of Mechanics, Energy Engineering and Applied Science (IJMEAS), 2025)
Dissimilar aluminum alloys welding between AA5xxx and AA6xxx presents significant challenges due toifferences in chemical composition, thermal properties, and electrochemical potential, all of which impact the corrosion resistance of the welded joints. AA5xxx alloys are well-known for their excellent corrosion resistance, particularly in marine environments, while AA6xxx alloys exhibit superior mechanical strength. This study provides a comprehensive investigation into the influence of various welding techniques—such as Gas Metal Arc Welding , Gas Tungsten Arc Welding , Laser Arc Welding, Laser Beam Welding, and Friction Stir Welding on the corrosion behavior of dissimilar joints between AA5xxx and AA6xxx. Each welding process induces distinct microstructural changes within the Fusion Zone and Heat-Affected Zone, which subsequently affect the joint's susceptibility to various corrosion mechanisms, including galvanic corrosion, intergranular corrosion, pitting corrosion, intermetallic corrosion, and stress corrosion cracking (SCC). Additionally, the difference in thermal expansion coefficients between AA5xxx and AA6xxx can generate residual stresses at the joint, exacerbating the risk of corrosion. This paper also explores mitigation strategies, including the optimization of welding parameters, the application of post-weld heat treatment, and the use of anticorrosive films through protective coatings to enhance corrosion resistance and extend the service life of the welded structures. The findings from this research offer comprehensive insights into the corrosion mechanisms in dissimilar alloys welding between AA5xxx-AA6xxx joints, providing practical guidance for optimizing welding processes. This paper aims to support the long-term performance of AA6xxx and AA5xxx aluminum alloy structures, particularly in critical industrial applications and environments demanding high corrosion resistance.